2009
DOI: 10.4039/n09-034
|View full text |Cite
|
Sign up to set email alerts
|

Transport of fungal symbionts by mountain pine beetles

Abstract: The perpetuation of symbiotic associations between bark beetles (Coleoptera: Curculionidae: Scolytinae) and ophiostomatoid fungi requires the consistent transport of fungi by successive beetle generations to new host trees. We used scanning electron microscopy and culture methods to investigate fungal transport by the mountain pine beetle (MPB), Dendroctonus ponderosae Hopkins. MPB transports its two main fungal associates, Grosmannia clavigera (Robinson-Jeffrey and Davidson) Zipfel, de Beer and Wingfield and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
0
34
1
Order By: Relevance
“…Such insects can carry fungal spores on their surface or in specialised structures such as mycangia which evolved in bark beetles as a means of transporting spores of mutualistic fungi (Bleiker et al, 2009;Grebennikov and Leschen, 2010;Masuya et al, 2009;Reay et al, 2005Reay et al, , 2006b. However, in this study, although the incidence of beetle colonisation increased with time, no difference was found in the proportion of sapstain present in discs as a function of beetle colonisation until the last sample time, 67 weeks after the storms in rooted trees.…”
Section: Discussioncontrasting
confidence: 79%
“…Such insects can carry fungal spores on their surface or in specialised structures such as mycangia which evolved in bark beetles as a means of transporting spores of mutualistic fungi (Bleiker et al, 2009;Grebennikov and Leschen, 2010;Masuya et al, 2009;Reay et al, 2005Reay et al, , 2006b. However, in this study, although the incidence of beetle colonisation increased with time, no difference was found in the proportion of sapstain present in discs as a function of beetle colonisation until the last sample time, 67 weeks after the storms in rooted trees.…”
Section: Discussioncontrasting
confidence: 79%
“…Other studies suggest that infestations are a function of more complex abiotic and biotic relationships between bark beetles and their hosts. These include reproductive and dispersal opportunities for bark beetles (Aukema et al, 2005;Roberston et al, 2009), transport and infection by fungi and other pathogens (Adams et al, 2008;Bleiker et al, 2009), predation and competition of bark beetles Schlyter and Anderbrant, 1993), fire (Breece et al, 2008;Fettig et al, 2008), and management practices (Waring and Pitman, 1985;Hayes et al, 2008). Although the results of these studies help us better understand local dynamics between bark beetles and their hosts, they are difficult to apply across large spatial or temporal scales.…”
Section: Introductionmentioning
confidence: 96%
“…As an example, Ophiostoma montium, which is more tolerant of warmer temperatures, has been found predominantly in MPB populations attacking during warmer periods [17]. It has been suggested that under a warming climate scenario, O. montium could displace G. clavigera [29] as the most important blue-stain fungal beetle associate; however, both species are found in most MPB populations [10,12,16,17,20,30]. Analyses of the effects of temperature on the stability of the above two blue-stain fungi have shown that beetle movement between warm and cold habitats, as well as variations in their attack densities, can help explain the prevalence of both species in the symbiosis [31].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the effects of temperature on the stability of the above two blue-stain fungi have shown that beetle movement between warm and cold habitats, as well as variations in their attack densities, can help explain the prevalence of both species in the symbiosis [31]. Thus, a fungal redundancy in the system may occur [10,21], but studies of fungal community trends during changing MPB populations have not been performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation